A bibliometric analysis of 100 top-cited journal articles related to acupuncture regulation of the autonomic nervous system - Zhao, Zhanhao; Li, Li; Xin, Chen; Yin, Yaqun; Zhang, Rong; Guo, Jing (Frontiers in Neuroscience, 2022)
Purpose: Research on the effects of acupuncture on autonomic function has been conducted for several decades, and a few notable studies have emerged in recent years. This study used bibliometric analysis to assess 100 top-cited articles to characterize the current status and research trends over the last three decades. Methods: The 100 top-cited publications were identified from the Web of Science Core Collection database. The bibliometrix package in R was used for quantitative and qualitative analyses of the publication patterns and the country/region, institution, and author contributions. VOSviewer was used to construct networks based on co-citation analysis of the journals and the keyword co-occurrence. Results: The 100 top-cited articles were identified with a total of 8,123 citations (range: 37-345). The majority of the articles came from the USA (n = 42), followed by Japan (n = 14) and mainland China (n = 13). Articles from the USA exhibited the largest number of citations (3,582 citations), followed by articles from Japan (1,189 citations), then articles from mainland China (755 citations). Neurosciences/Neurology was the most studied research area (n = 41). The Autonomic Neuroscience: Basic & Clinical published the largest number of papers (n = 14), while Brain Research received the largest number of citations (205 citations). Longhurst JC was the most productive author (10 publications), and Sato A was first among the cited authors (87 citations). The most frequently cited articles that focused on gastrointestinal, cardiovascular, or gynecologic responses to acupuncture regulation of the autonomic nervous system first appeared in the 1990s, peaked in the 2000s, then decreased after 2010. Publication of articles focused on the anti-inflammatory effects of acupuncture associated with autonomic function demonstrated an increasing trend over the last three decades. Conclusions: From the initial studies focusing on the autonomic mechanism of visceral responses to acupuncture, researchers concentrated on exploring the autonomic mechanism of acupuncture in the control of systemic inflammation. Noninvasive electrical methods that activate somato-autonomic reflexes are current translational directions in clinical practice. Additional investigation of the underlying neuroanatomical basis of somato-autonomic reflexes also is needed.